Just another day's work: The nexus between workplace experiences and Post-Traumatic Stress Disorder (PTSD) in jail settings. (July 2022) - Ellison, Jared M.; Cain, Calli M.; Jaegers, Lisa A.
Abstract: Purpose: Correctional officers experience more workplace violence and victimization than individuals in comparable public service occupations, and such experiences may lead to higher levels of post-traumatic stress disorder (PTSD). Methods: In this study, we examine the officer- and facility-level correlates of PTSD among 1327 officers working in 20 jails and consider the relationships between exposure to violence (ETV), workplace stressors, personal demographics or experiences, and PTSD indicators. Results: Our results suggested that officers who were assaulted or were threatened more often, who witnessed more staff assaults, and who perceived unreasonable workloads or greater role problems at work were more likely to exhibit PTSD symptoms. However, officers with greater family support, males, and non-white officers had a lower propensity for PTSD. Conclusions: Jail workforces that perceived more dangerous conditions, greater role problems, and more daily interaction with those they supervised had higher levels of PTSD. Implications for research and policy are discussed. Highlights: Violent and stressful jail environments make officers especially vulnerable to Post-Traumatic Stress Disorder (PTSD). We examine the link between dangerous and stressful work conditions and PTSD across 1, 327 officers working in 20 jails. Exposure to violence, unreasonable work demands, greater role problems, and less family support increased the risk of PTSD. Dangerous jails and those where the workforce perceived more unclear or conflicting policies had greater levels of PTSD. The PCL-5 was a useful screening tool for PTSD and may inform efforts to preserve the health and safety of jail officers.